LEGAL CHALLENGES POSED BY MODERN DAY PIRACY: CASE STUDIES OF FRANCE, ITALY AND SPAIN - Kiss, Amarilla (POLARITIES, 2023)
Maritime piracy is an ancient menace threatening the freedom of navigation and maritime security. The international community has always been triggered by it and pirates became the enemies of all mankind. Currently, the seas provide nearly 90% of the world trade. Around 90% of the EU’s external trade is carried out at sea. In the northern Mediterranean region, France, Italy and Spain are especially involved. Ensuring maritime security is not only a military issue but it starts with legal regulations and continues in courtrooms. Therefore, the paper explores how affected states respond to the challenges posed by piracy. The research compares states on the basis of the concept of piracy, the attitude towards the employment of private maritime security companies and the judicial practice, relevant cases.